Ultra-low temperature vitrified bond, preparation method therefor, ceramic diamond wheel including ultra-low temperature vitrified bond and preparation method therefor
The development of ultra-low temperature vitrified bonds with a sintering temperature of 400°C addresses the challenges of diamond oxidation and heavy metal contamination in existing technologies, enabling the production of ultra-fine abrasive ceramic diamond wheels with improved mechanical properties and grinding performance.
Patent Information
- Application Number
- JP2023214545
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-12
- Filing Date
- 2023-12-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-12-20
AI Technical Summary
Current vitrified bonds for ultra-fine abrasive diamond wheels require high sintering temperatures, leading to oxidation of diamonds and inability to meet the sintering requirements for ultra-fine abrasive ceramic diamond wheels, while also containing harmful heavy metals.
Development of ultra-low temperature vitrified bonds with a sintering temperature as low as 400°C, composed of Bi2O3, B2O3, ZnO, SiO2, Li2O, TiO2, CaF2, and Y2O3, which maintains mechanical strength and allows for effective bonding and fixation before polymer pore forming agents and binders decompose.
The ultra-low temperature vitrified bonds prevent high-temperature oxidation of ultra-fine abrasive diamonds, enable the preparation of wheels with high porosity and controlled pore size, and provide good wettability and bond strength with diamonds, resulting in improved grinding performance and extended wheel life.
Smart Images

Figure 2025040919000013 
Figure 2025040919000014 
Figure 2025040919000015
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of ultra-precision machining preparation of hard and brittle materials, and specifically to a vitrified bond for ultra-low temperature sintering and a method for preparing an ultra-fine grain diamond wheel using the same for ultra-precision machining of hard and brittle materials. [Background technology]
[0002] Vitrified bond wheels (wheels using vitrified bonds) have excellent grinding ability, excellent shape retention, high grinding precision, less clogging, easy maintenance and shaping, excellent resistance to high temperatures, acid and alkali, and are suitable for grinding with various coolants and various processing precision requirements, so they are the most widely used. Ultrafine abrasive wheels (abrasive grain size of 10 μm or less) are usually used in ultra-precision processing, especially in the fields of integrated circuits, semiconductor power devices and optoelectronic devices. In these fields, hard and brittle materials such as single crystal silicon, sapphire, silicon carbide, lithium tantalate, and gallium nitride are used, and the requirements for wafer flatness and surface quality are very high. Therefore, using ultrafine abrasive vitrified bond diamond wheels (diamond wheels using vitrified bonds) for precision grinding is an essential part, and the quality of this processing determines the product yield rate.
[0003] In the preparation of vitrified bond diamond wheels, the vitrified bond is melted by sintering to bond the diamond, forming a diamond wheel with a certain strength and shape. However, diamond is a carbon-based material, and if sintered in an air atmosphere, it will be oxidized at high temperatures (generally, the oxidation temperature of coarse diamond in an air atmosphere is about 700°C), and fine diamond will be oxidized at 600°C when sintered in an air atmosphere, which will cause the wheel performance to deteriorate. The sintering temperature of the current vitrified bond for diamond is generally 700-800°C, which cannot meet the sintering requirements for preparing ceramic diamond wheels with ultrafine abrasive grains. Previously, a vitrified bond for diamond with a sintering temperature of 600°C or less was developed, but the vitrified bond for diamond contains a large amount of PbO as a melting-promoting component to lower the sintering temperature of the vitrified bond, and the heavy metal lead is highly damaging to the ecological environment and human health, so its use has been restricted or prohibited worldwide. For this reason, the bond has not been widely used. For this reason, there is a strong demand to develop a contamination-free vitrified bond that is suitable for ultra-low temperatures (sintering temperature of 600°C or less) and to prepare diamond wheels with ultra-fine abrasive grains.
[0004] The sintering temperature of the vitrified bond is a temperature range that can melt the vitrified bond sufficiently to spread it on the surface of the abrasive and satisfy the bonding performance between the abrasives. In production, a standard flow block prepared by the bond, i.e., a cylinder with a diameter and height of 15 mm, is generally used to represent the deformation state of the standard flow block at different temperatures, thereby representing the flow and spreading ability of the bond on the surface of the abrasive. Specifically, the fluidity of the bond is represented by measuring the percentage of the diameter of the sample after sintering to the initial diameter of the standard flow block. Usually, the sintering temperature range is the temperature at which the fluidity of the bond is 90% to 160%, and the temperature corresponding to the time when the corners of the sample start to become arc-shaped by heating is the melting start temperature T1 of the bond, which is the lower limit temperature at which the vitrified bond can be used to prepare a wheel, and the fluidity at this time is usually about 90%. When the temperature reaches T2, the sample becomes hemispherical, its height is about 2 / 3 of the initial sample height, T2 is the melting temperature of the bond, at this time the bond has already melted and is in a viscous flow state, its fluidity is about 120%. When heated to T3, the sample flows and spreads, its height is about 1 / 3 of the initial sample height, T3 is the flowing temperature when it is made into a glaze, its fluidity is usually about 160%. Specifically, as shown in Figure 1. The temperature range from T1 to T3 is the sintering temperature range of the bond.
[0005] In addition, the finer the grain size of the wheel abrasive, the poorer the cutting ability and self-sharpening ability of the grinding tool. In order to ensure the continuity of cutting ability during the wafer flattening process and to avoid the warping, deformation and processing damage layer of the wafer caused by the grinding stress generated on the grinding surface of the wafer, in addition to forming a certain pore structure by the natural deposition of abrasive grains, a pore-forming material is generally added to form an additional pore structure, which moderately weakens the strength of the structure and improves the self-sharpening ability of the wheel. The shape of the internal pores generated by the conventional pore-forming agent is irregular, the size of the pores varies greatly, and the porosity cannot be effectively controlled, making it difficult to design and control the pore structure of the ultrafine abrasive wheel. Then, the method of adding polymeric spherical pore-forming agent is adopted, and the size and porosity of the pores are positively correlated with the particle size and the amount of the pore-forming agent added, so that by controlling the particle size and the amount of the polymeric pore-forming agent added, it is possible to obtain wheel pores with a spherical structure, and the negative impact of shortening the life of the pore structure can be effectively reduced. However, when this process is adopted, only a pore structure with a porosity of 50Vol% or less can be obtained, because a large amount of spherical polymer material must be added to obtain a structure with high porosity, and the friction force between the powder materials is relatively small, so that the polymeric pore-forming agent is burned out at high temperatures and fixed without a binder, and the structure cannot be maintained. Press molding can be achieved by using a temporary polymer binder, but the polymer binder and pore former are completely decomposed and burned away at a temperature of 450°C, and are no longer able to play the role of temporary binding and supporting skeletal deposition. At this temperature, all vitrified bonds have not reached the melting start temperature, and the structure cannot be fixed, and the molding body collapses and becomes unusable (see Figure 2). Therefore, the preparation of a wheel structure with a high volume fraction of porosity is not simply determined by the pore former, but the vitrified bond has a binding effect on the structure with a high volume fraction of porosity, so after the polymer temporary binder and pore former materials are deactivated and no longer able to be bonded or burned away at a temperature of 450°C, it is necessary to lower the melting start temperature of the bond so that the vitrified bond has appropriate binding and fixing strength and maintains the macrostructure of the body.
[0006] Therefore, how to scientifically design the components of the vitrified bond to lower the sintering temperature range of the bond while maintaining good mechanical strength and maximally protecting the strength of the diamond particles themselves, and how to design and control the high porosity pore structure of an ultra-fine abrasive wheel using a vitrified bond are important technical issues in the field of ultra-fine abrasive ceramic diamond wheels for ultra-precision planarization of semiconductor hard and brittle wafer materials.
[0007] In order to solve the above problems, the following patent technologies have been developed. (1) The composition (by mass) of the low-temperature vitrified bond described in Patent Document 1, "Low-temperature sintered vitrified bond and its preparation method" includes 30-35 parts of silica sol, 45-50 parts of bismuth (III) oxide, 5-7 parts of boric acid, and 12-20 parts of additives (3-5 parts of zinc oxide, 3-5 parts of manganese dioxide, 3-5 parts of iron (III) oxide, and 3-5 parts of divanadium pentoxide). The patent technology mainly emphasizes the low-temperature sintering performance of the vitrified bond, which can effectively prevent the oxidation of diamond due to high temperature, but does not mention the strength performance of the bond and its effect on the hole-making process. (2) Patent Document 2, "Low-temperature vitrified bond diamond wheel and preparation method thereof," also adopts a low-temperature glass system of bismuth oxide (III)-boron oxide (Bi2O3-B2O3), and the composition (molar percentage) of the low-temperature vitrified bond includes 30%-50% bismuth oxide (III), 30%-50% boron oxide, 2%-10% silicon dioxide, and 2%-10% aluminum oxide. This patent technology also mainly emphasizes the low-temperature sintering characteristics of the vitrified bond, and although this patent technology uses walnut shells as a pore-forming agent, it adopts conventional material selection and has no relationship between the bond and the pore-forming process. (3) Patent Document 3, "Vitrified bond wheel and preparation method thereof," describes a method for preparing an ultrafine abrasive vitrified bond wheel having a high porosity with a volume fraction of 75 to 95%, in which the sintering temperature of the vitrified bond used is 700°C, which can prevent high-temperature oxidation of general coarse diamond. However, the sintering temperature is still relatively high for ultrafine diamond. Polystyrene particles of 30 to 100 μm are used as a pore-forming agent, and sodium silicate is especially added as a medium-temperature (approximately 400 to 600°C) binder, thereby maintaining the shape of the base body at high temperatures and preventing the base body from collapsing after sintering, which is caused by the polymer molding binder losing its effectiveness at high temperatures (450°C or higher) and becoming unable to bind.However, because a relatively large amount of sodium silicate (Na2O·nSiO2) is used, a relatively large amount of Na2O is introduced into the bond. In this case, the strength of the bond is reduced, which is disadvantageous to the life of the wheel, and the abrasive grains are likely to be abnormal and fall out unexpectedly, which will lead to accidental scratches in ultra-precision machining, which is unacceptable for practical use. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Patent CN201711006994.8 [Patent Document 2] Patent CN202210952515.6 [Patent Document 3] Patent CN200510072858.X Summary of the Invention [Problem to be solved by the invention]
[0009] Previous patent applications have addressed the problem of preparing ultrafine ceramic diamond wheels, especially ultrafine ceramic diamond wheels with high porosity, by only using low-temperature vitrified bond or hole-making processes, and have not designed a comprehensive solution from the standpoint of collaboration. Wheels prepared in this way have difficulty in achieving a balance between sharpness and durability, and are difficult to meet the technical requirements of high efficiency, low damage and long life for wheels in ultra-precise planarization of semiconductor wafers. In view of the above, the present invention has been devised. [Means for solving the problem]
[0010] The present invention aims to overcome the shortcomings of the prior art and provide a super low temperature vitrified bond, which has good mechanical strength, a sintering temperature of at least 400°C, a bond softening point temperature of at least 320°C, and can maintain the binding and fixing function of the vitrified bond before the polymeric pore former and polymeric temporary binder are burned off, so that it has a relatively high porosity and maintains the integrity of the pore structure, and by using this vitrified bond and a preferred polymeric pore former, it is possible to form spherical pores in which the microscopic gaps of the pores are connected, and the size of the pores can be controlled during preparation.
[0011] The present invention further provides a method for preparing an ultra-fine grain ceramic diamond wheel using the above cryogenic vitrified bond.
[0012] To achieve the above objectives, the present invention adopts the following technical solutions.
[0013] The raw materials of ultra-low temperature vitrified bond are mainly composed of Bi2O3: 40-80%, B2O3: 5-15%, ZnO: 10-35%, SiO2: 0-5%, Li2O: 0.5-3%, TiO2: 0-5%, CaF2: 2-10%, and Y2O3: 0-5% by mass fraction. Preferably, the mass ratio of Bi2O3 to ZnO is 1.5-5.5:1.
[0014] The present invention provides a low-temperature vitrified bond, which contains, as components by mass fraction, 40-80% Bi2O3, 5-15% B2O3, 10-35% ZnO, 0-5% SiO2, 0.5-3% Li2O, 0-5% TiO2, 2-10% CaF2, and 0-5% Y2O3.
[0015] The Bi2O3 component of the ultra-low temperature vitrified bond according to the present invention can lower the softening point temperature of the bond, improve the fluidity of the bond, and lower the temperature of crystal precipitation. At high temperatures, B2O3 exists as a boron-oxygen triangle, which reduces the viscosity and is favorable for melting. At low temperatures, B2O3 is formed as a boron-oxygen tetrahedron, which makes the structure tighter and is favorable for improving strength. Li2O can reduce the linear expansion coefficient and devitrification tendency of the glass. ZnO can lower the glass melting temperature of the bond, adjust the thermal expansion coefficient, and when used together with optional TiO2, it facilitates the precipitation of small equiaxed crystal forms. CaF2 can lower the melting point of the glass, which is favorable for improving the impact resistance of the glass. Optional SiO2 can reduce the crystallization tendency of the glass and is favorable for the refinement of the crystal grains. Optional Y2O3 is a rare earth oxide, which can suppress the devitrification of the glass and realize the refinement of the crystal grains.
[0016] The ultra-low temperature vitrified bond according to the present invention contains, as components, by mass fraction, Bi2O3: 40-70%, B2O3: 5-12.5%, ZnO: 12.5-35%, SiO2: 1-5%, Li2O: 0.5-3%, TiO2: 0-5%, CaF2: 2-10%, and Y2O3: 0-5%.
[0017] The ultra-low temperature vitrified bond according to the present invention has a mass ratio of Bi2O3 to ZnO of 1.5 to 5.5:1.
[0018] As the Bi2O3 / ZnO value of the components of the ultra-low temperature vitrified bond according to the present invention increases, the improving effect of lowering the sintering temperature of the bond becomes weaker and weaker, so it is preferable to keep the Bi2O3 / ZnO value within the above range.
[0019] The ultra-low temperature vitrified bond according to the present invention satisfies at least one of the following characteristics a to c: a. 10 to 20 μm; b. softening point temperature is 320 to 395°C, optionally 320 to 385°C; c. sintering temperature is 400 to 485°C, optionally 400 to 470°C.
[0020] The present invention provides a method for preparing a vitrified bond at very low temperature, the method comprising the steps of:
[0021] Step (1): Mix the raw materials uniformly with mass fractions of Bi2O3: 40-80%, B2O3: 5-15%, ZnO: 10-35%, SiO2: 0-5%, Li2O: 0.5-3%, TiO2: 0-5%, CaF2: 2-10% and Y2O3: 0-5% to obtain a mixed material. Step (2): The mixed material is melted in a high-temperature smelting furnace at a temperature of 900 to 1100° C. for 40 to 120 minutes using a quartz crucible to obtain molten glass. Step (3): The molten glass is water quenched, polished using a stirring mill, and dried to obtain an ultra-low temperature vitrified bond with a particle size of 10 to 20 μm.
[0022] The sintering temperature range of the prepared ultra-low temperature vitrified bond is 400-470°C. The softening point of the vitrified bond is as low as 320°C, which is lower than the decomposition temperature of some polymeric pore formers and polymeric binders, and the bond has good wettability with diamond (see Figure 3). The strength test piece prepared using the bond and diamond has a flexural strength of 50-65 MPa and an impact strength of 8-15 KJ / m 2 It is.
[0023] In one embodiment of the present invention, the mass fractions of the raw materials are as follows: Bi2O3: 40-70%, B2O3: 5-12.5%, ZnO: 12.5-35%, SiO2: 1-5%, Li2O: 0.5-3%, TiO2: 0-5%, CaF2: 2-10%, and Y2O3: 0-5%.
[0024] In one embodiment of the present invention, the mass ratio of Bi2O3 to ZnO in the raw materials is 1.5-5.5:1.
[0025] In one embodiment of the present invention, the Bi2O3, ZnO, SiO2, TiO2, CaF2, and Y2O3 in the raw materials are analytical grade compounds themselves, the raw material for B2O3 is analytical grade boric acid, and the raw material for Li2O is analytical grade lithium carbonate.
[0026] When boric acid is used as the initial raw material instead of B2O3, the amount of boric acid used is 1.8 times that of B2O3. If lithium carbonate is used as the initial raw material instead of Li2O, the amount of lithium carbonate used is 2.47 times that of Li2O.
[0027] When at least one of boric acid and lithium carbonate is used as the initial raw material, in step (2), the mixed material is subjected to dehydration at a temperature of 350 to 450°C (for about 40 to 60 minutes), and then melted in a high-temperature smelting furnace at a temperature of 900 to 1100°C for 40 to 120 minutes using a quartz crucible to obtain molten glass.
[0028] More preferably, in step (3), the parameters of polishing with an agitating mill are that the rotation speed of the agitating mill is 800 to 900 rpm, wet milling is used, the mass ratio of water to material is 1 to 1.5:1, the polishing medium is zirconia balls (diameter 5 to 7 mm), the mass ratio of balls to material is 2 to 4:1, and ball milling is performed for 0.5 to 2 hours.
[0029] The present invention further provides an ultrafine grain ceramic diamond wheel prepared using the ultra-low temperature vitrified bond, which is prepared from raw materials mainly consisting of 15-35% ultra-low temperature vitrified bond, 20-75% diamond abrasive, and 10-55% polymer pore former, in terms of mass fraction.
[0030] Specifically, the polymeric pore-forming agent is one or two of polyethylene particles, polytetrafluoroethylene particles, etc., and the amount and particle size thereof can be adjusted according to needs. The particle size of the polymeric pore-forming agent is 20 to 400 μm.
[0031] Furthermore, the diamond abrasive has a particle size of 0.5 to 5 μm.
[0032] The present invention provides a ceramic diamond wheel comprising the above-described ultra-low temperature vitrified bond.
[0033] In one embodiment of the present invention, the ceramic diamond wheel contains, as components, 15 to 35 parts by mass of ultra-low temperature vitrified bond and 20 to 75 parts by mass of diamond abrasive, and the porosity of the ceramic diamond wheel is 35 to 95 vol %.
[0034] In one embodiment of the present invention, the diamond abrasive has a particle size of 0.5 to 5 μm.
[0035] In one embodiment of the present invention, the porosity of the ceramic diamond wheel is 40-95 vol%, optionally 70-95 vol%, optionally 75-95 vol%, and / or the pore size is 20-800 μm, which can be controlled as required.
[0036] The present invention further provides a method for preparing the ultrafine grain ceramic diamond wheel, which is specifically as follows:
[0037] A mixed material is obtained by uniformly mixing, in mass fraction, 15-35% ultra-low temperature vitrified bond, 20-75% diamond abrasive, and 10-55% polymeric pore-forming agent, and 5-10% of a phenolic resin alcohol solution is added to the mixed material so that the mass concentration of the phenolic resin alcohol solution is 25%-35%. The mixed material is then wetted, sieved, and granulated. The granulated mixed material is press-molded and dried, and then sintered at a temperature of 400-485°C in an air atmosphere, and the temperature is maintained for 3.5-5 hours to obtain the ultrafine abrasive ceramic diamond wheel.
[0038] In one embodiment of the present invention, sintering is carried out at a temperature of 400 to 470° C. in an air atmosphere, and the temperature is maintained for 3.5 to 5 hours to obtain the ultrafine grain ceramic diamond wheel.
[0039] An ultrafine abrasive ceramic diamond wheel is prepared, in which the pore shape is spherical and the porosity (35-95 vol%) and pore size (20-800 μm) can be controlled.
[0040] Specifically, the polymeric pore-forming agent is one or two of polyethylene particles, polytetrafluoroethylene particles, etc., and the amount and particle size thereof can be adjusted according to needs. The particle size of the polymeric pore-forming agent is 20 to 400 μm.
[0041] In particular, in the present invention, polytetrafluoroethylene particles having a relatively high decomposition temperature are used to prepare a wheel using an ultrafine abrasive diamond vitrified bond with a porosity of over 75 vol%, and the decomposition temperature of polytetrafluoroethylene particles is 420°C, which is higher than the softening point temperature of the bond according to the present invention, which is 320-395°C, and this can effectively prevent the ceramic body from collapsing after the polymer material is burned off. In addition, in the preparation of a wheel structure with ultra-high porosity, it is necessary to design a temperature curve that is longer than the conventional general heat retention time, and in the present invention, heat retention is performed for 3.5-5 hours, and an ultrafine abrasive vitrified bond diamond wheel with a high porosity of 95 vol% can be prepared. Effect of the Invention
[0042] (1) The ultra-low temperature vitrified bond according to the present invention has an ultra-low sintering temperature, with the sintering temperature range being 400-485°C. This effectively prevents high-temperature oxidation of ultra-fine diamond abrasive grains during the sintering process in an air atmosphere, and the softening point temperature of the vitrified bond according to the present invention is low, with the softening point temperature of the bond being as low as 320°C at the lowest, lower than the decomposition temperature of some polymeric pore formers and polymeric binders, so that the binding and fixing action of the vitrified bond can be maintained before the polymeric pore formers and polymeric temporary binders are burned off, and a wheel using an ultra-fine vitrified bond with a high porosity and controllable pore size can be prepared using the bond.
[0043] (2) The ultra-low temperature vitrified bond according to the present invention has good wettability and bond strength with diamond, and also has relatively good impact strength, and can be used in grinding under severe operating conditions involving impact.
[0044] (3) The vitrified bond according to the present invention has a low sintering temperature and does not contain heavy metal oxides such as As2O3, PbO, BaO, and V2O5 that are harmful to the environment, and is therefore environmentally friendly.
[0045] (4) In the present invention, a polytetrafluoroethylene pore former material with a relatively high decomposition temperature (melting point: 327°C, decomposition temperature: 420°C) is adopted, which is compatible with the softening temperature and sintering temperature of the ultra-low temperature bond of the present invention, thereby making it possible to prepare an ultra-fine abrasive ceramic diamond wheel with a porosity of 75 vol% or more and controllable pore size.
[0046] (5) The ultra-low temperature vitrified bond of the present invention has good mechanical strength, can be well bonded with diamond, and has spherical pores, which contributes to ensuring the strength of the macrostructure. Therefore, when used in the ultra-precision flattening of semiconductor wafers, the surface processing quality is relatively high, the processing damage is relatively low, and the wheel service life is good. [Brief description of the drawings]
[0047] [Figure 1] FIG. 2 is a schematic diagram showing a change in a vitrified bond at high temperatures. [Diagram 2] FIG. 11 is a comparison diagram of the base body of a conventional wheel block with high porosity before and after sintering: (a) the wheel block with high porosity has a perfectly shaped formed base body, and (b) the wheel block with high porosity has a crumbled base body after sintering. [Diagram 3] 1 is a micrograph showing the wetting bond between the ultra-low temperature vitrified bond and diamond according to the present invention. [Figure 4] 1 is an actual photograph showing a flow state of the ultra-low temperature vitrified bond according to Example 1 of the present invention. [Diagram 5] 1 is a micrograph of the structure of an ultrafine grain ceramic diamond wheel according to Example 1 of the present invention. [Figure 6] 11 is an actual photograph showing the flow state of the ultra-low temperature vitrified bond according to Example 2 of the present invention. [Figure 7] 1 is a micrograph of the structure of an ultrafine grain ceramic diamond wheel according to Example 2 of the present invention. [Figure 8] 11 is an actual photograph showing the flow state of the ultra-low temperature vitrified bond according to Example 3 of the present invention. [Figure 9] 1 is a micrograph of the structure of an ultrafine grain ceramic diamond wheel according to Example 3 of the present invention. [Figure 10] 1 is a micrograph of the structure of an ultrafine grain ceramic diamond wheel according to Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0048] The technical solution of the present invention will be described in more detail with reference to the following examples, which do not limit the scope of the present invention.
[0049] Unless otherwise specified, "A and / or B" in this specification means "at least one of A and B." In the following examples, unless otherwise specified, all the raw materials used are commercially available or can be prepared by conventional methods (for example, phenolic resin can be directly purchased and then diluted and dissolved in alcohol to a suitable concentration to obtain a phenolic resin alcohol solution with a mass concentration of 25% to 35%), and operations or steps (for example, granulation, etc.) that are not described in detail can be performed by conventional techniques in the art.
[0050] As used herein, unless otherwise specified, the low-temperature vitrified bond described herein refers to a vitrified bond having a relatively low sintering temperature. Generally, the low-temperature vitrified bond refers to a vitrified bond having a sintering temperature of 850°C to 1050°C. As used herein, unless otherwise specified, the ultra-low temperature vitrified bond described herein refers to a vitrified bond with an ultra-low sintering temperature. Generally, the ultra-low temperature vitrified bond refers to a vitrified bond with a sintering temperature of less than 600° C.
[0051] As used herein, the terms "particle size," "particle size," and "particle size" refer to particle size, and unless otherwise specified, these terms are used interchangeably. In this specification, unless otherwise specified, the particle size or particle diameter or pore size refers to particle size distribution, which is generally measured using a laser particle size measuring device.
[0052] In this specification, the term "flexural strength" refers to the strength value obtained by performing a three-point bending test on a test piece manufactured from a vitrified bond and diamond. The measurement method was to mix a vitrified bond sample with a mass fraction of 18% and a diamond with a mass fraction of 82%, press the mixture, and test it to a density of 1.85 g / cm3. 3 A test piece having dimensions of 50 mm×6 mm×5 mm is manufactured, and after sintering the test piece at a predetermined sintering temperature, the flexural strength is measured using a triaxial bending strength tester. As those skilled in the art will appreciate, the strength of the vitrified bond can be measured using a test piece made of the vitrified bond and diamond, since the vitrified bond and diamond work together as a wheel. Without wishing to be bound by any theory, the flexural strength of the diamond strength test piece shows a positive correlation with the strength of the vitrified bond itself.
[0053] In the embodiment, Bi2O3, ZnO, SiO2, TiO2, CaF2, and Y2O3 are used as raw materials of analytical grade compounds themselves, the raw material of B2O3 is analytical grade boric acid, and the raw material of Li2O is analytical grade lithium carbonate. As those skilled in the art will understand, when using boric acid water, B2O3 is obtained by removing water of crystallization. When using lithium carbonate, Li2O is obtained in a high temperature environment. Other components and contents do not change before and after the preparation of the bond.
[0054] [Example 1] 1. Preparation of Bond The raw materials were mixed according to the mass fractions shown in Table 1 below, and the mixed materials were uniformly mixed using a three-dimensional mixer, and dehydrated in a high-temperature oven at a temperature of 400 ° C for 60 minutes. Then, in a high-temperature smelting furnace, a quartz crucible was used to melt the mixture at a temperature of 1100 ° C for 40 minutes to obtain molten glass, and the molten glass in the molten state was put into water to perform water quenching, and then finely ground using a stirring mill (the rotation speed of the stirring mill was 840 rpm, wet milling was used, the mass ratio of water to material was 1:1, the polishing medium was a zirconia ball with a diameter of 5 to 7 mm, and the ratio of ball to material was 3:1), ball milling was performed for 1 hour, and the mixture was dried at a temperature of 150 ° C for 10 hours to obtain an ultra-low temperature vitrified bond with a particle size of 10 to 20 μm.
[0055] [Table 1]
[0056] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 385°C and a sintering temperature of 470°C. The fluidity at a temperature of 470°C is shown in Figure 4, where the fluidity was 130%, and the material was in a molten state, showing a good fluidity. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 65 MPa and an impact strength of 15 KJ / m 2 It was.
[0057] 2. Preparation of Ceramic Diamond Wheel The above-mentioned ultra-low temperature vitrified bond thus prepared was weighed out at 15% by mass, diamond abrasive with a particle size of 2-4 μm at 70%, and polymeric pore former with a particle size of 20-50 μm (polyethylene particles and polytetrafluoroethylene particles with a mass ratio of 1:3 at 15%) at 15%, and the above materials were uniformly mixed to obtain a mixed material for the wheel. The mixed material was then wetted for 10 minutes with a 5% phenolic resin alcohol solution (concentration was 25%) and passed through a 60 mesh sieve five times. The mixture was filtered to mix uniformly and granulated, and the granulated mixed material was molded and pressed, dried (12 hours at room temperature and 12 hours in a 50°C oven, for a total of 24 hours, as below), and then placed in a furnace and sintered in an air atmosphere. The sintering temperature was 470°C and the heat retention time was 3.5 hours. This resulted in an ultra-fine abrasive ceramic diamond wheel (see Figure 5) with spherical pores, a porosity of 45 vol%, and a pore size of 20 to 50 μm.
[0058] [Example 2] 1. Preparation of Bond The raw materials were mixed according to the mass fractions shown in Table 2 below, and the mixed materials were uniformly mixed using a three-dimensional mixer, and dehydrated in a high-temperature oven at a temperature of 400 ° C for 60 minutes. Then, in a high-temperature smelting furnace, a quartz crucible was used to melt the mixture at a temperature of 1000 ° C for 90 minutes to obtain molten glass, and the molten glass in the molten state was put into water to perform water quenching, and then finely ground using a stirring mill (the rotation speed of the stirring mill was 840 rpm, wet milling was used, the mass ratio of water to material was 1:1, the polishing medium was a zirconia ball with a diameter of 5 to 7 mm, and the ratio of ball to material was 3:1), ball milling was performed for 1 hour, and the mixture was dried at a temperature of 150 ° C for 10 hours to obtain an ultra-low temperature vitrified bond with a particle size of 10 to 20 μm.
[0059] [Table 2]
[0060] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 340°C and a sintering temperature of 440°C. The fluidity at a temperature of 440°C is shown in Figure 6, where the fluidity was 130%, and the material was in a molten state, with a good fluidity. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 55 MPa and an impact strength of 12 KJ / m 2 It was.
[0061] 2. Wheel Preparation The above ultra-low temperature vitrified bond thus prepared was weighed out at 35% by mass, diamond abrasive with a particle size of 1-2 μm at 35%, and polymeric pore former with a particle size of 20-400 μm (polyethylene particles and polytetrafluoroethylene particles with a mass ratio of 1:2 at 30%) at 30%, and the above materials were uniformly mixed to obtain a mixed material for the wheel. The mixed material was wetted for 10 minutes with an 8% phenolic resin alcohol solution (concentration was 30%) added to the mass of the mixed material, and the mixture was uniformly mixed and granulated by passing through a 60 mesh sieve five times. The granulated mixed material was molded and pressed, dried, and then placed in a furnace and sintered in an air atmosphere. The sintering temperature was 440°C, and the warming time was 4 hours. As a result, an ultra-fine abrasive ceramic diamond wheel (see FIG. 7) with a spherical pore shape, a porosity of 70 vol%, and a pore size of about 35-470 μm was obtained.
[0062] [Example 3] 1. Preparation of Bond The raw materials were mixed according to the mass fractions shown in Table 3 below, and the mixed materials were uniformly mixed using a three-dimensional mixer, and dehydrated in a high-temperature oven at a temperature of 400 ° C for 45 minutes. Then, in a high-temperature smelting furnace, a quartz crucible was used to melt the mixture at a temperature of 900 ° C for 120 minutes to obtain molten glass, and the molten glass in the molten state was put into water to perform water quenching, and then finely ground using a stirring mill (the rotation speed of the stirring mill was 840 rpm, wet milling was used, the mass ratio of water to material was 1:1, the polishing medium was a zirconia ball with a diameter of 5 to 7 mm, and the ratio of ball to material was 3:1), ball milling was performed for 1 hour, and the mixture was dried at a temperature of 150 ° C for 10 hours to obtain an ultra-low temperature vitrified bond with a particle size of 10 to 20 μm.
[0063] [Table 3]
[0064] The ultra-low temperature vitrified bond prepared in this embodiment has a softening temperature of 320°C and a sintering temperature of 400°C. The fluidity state at a temperature of 400°C is shown in Figure 8, where the fluidity is 110% and the melting start state is close to the molten state, so the fluidity state meets the requirements. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 50 MPa and an impact strength of 8 KJ / m 2 It was.
[0065] 2. Wheel Preparation The above ultra-low temperature vitrified bond thus prepared was weighed out at 25% by mass, diamond abrasive with a particle size of 0-0.5 μm at 20%, and polytetrafluoroethylene polymer pore former with a particle size of 30-300 μm at 55% by mass. The above materials were uniformly mixed to obtain a mixed material for the wheel. A 10% phenolic resin alcohol solution (concentration was 35%) was added to the mass of the mixed material, and the mixture was wetted for 10 minutes. The mixture was passed through a 60 mesh sieve five times to uniformly mix and granulate. The granulated mixed material was molded and pressed, dried, and then placed in a furnace to be sintered in an air atmosphere. The sintering temperature was 400°C, and the warming time was 5 hours. As a result, an ultra-fine abrasive ceramic diamond wheel (see FIG. 9) with a spherical pore shape, a porosity of 95 vol%, and a pore size of about 50-350 μm was obtained.
[0066] [Example 4] 1. Preparation of Bond The raw materials were blended according to the mass fractions shown in Table 4 below, and the preparation process and parameters of the bond according to Example 1 were followed to obtain ultra-low temperature vitrified bond with grain size of 10-20 μm.
[0067] [Table 4]
[0068] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 395°C and a sintering temperature of 485°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 53 MPa and an impact strength of 8 KJ / m 2 It was.
[0069] 2. Preparation of Ceramic Diamond Wheel According to the preparation process and parameters of the ceramic diamond wheel according to Example 1, an ultrafine abrasive ceramic diamond wheel was obtained, in which the pore shape was spherical, the porosity was 45 vol%, and the pore size was 20-50 μm.
[0070] [Example 5] 1. Preparation of Bond The raw materials were blended according to the mass fractions shown in Table 5 below, and the preparation process and parameters of the bond according to Example 1 were followed to obtain ultra-low temperature vitrified bond with grain size of 10-20 μm.
[0071] [Table 5]
[0072] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 370°C and a sintering temperature of 460°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 55 MPa and an impact strength of 7 KJ / m 2 It was.
[0073] 2. Preparation of Ceramic Diamond Wheel According to the preparation process and parameters of the ceramic diamond wheel according to Example 1, an ultrafine abrasive ceramic diamond wheel was obtained, in which the pore shape was spherical, the porosity was 45 vol%, and the pore size was 20-50 μm.
[0074] [Example 6] 1. Preparation of Bond The steps were the same as in Example 3, but the only difference from Example 3 was that the mass fractions of the raw materials were different. The mass fractions of the raw materials are shown in Table 6.
[0075] [Table 6]
[0076] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 330°C and a sintering temperature of 415°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 48 MPa and an impact strength of 7 KJ / m 2 It was.
[0077] 2. Wheel Preparation A ceramic diamond wheel was prepared according to the preparation process and parameters of the ceramic diamond wheel in Example 3. An ultrafine abrasive ceramic diamond wheel was obtained, in which the pore shape was spherical, the porosity was 90 vol%, and the pore size was about 50-350 μm.
[0078] [Example 7] 1. Preparation of Bond The raw materials were blended according to the mass fractions shown in Table 7 below, and the preparation process and parameters of the bond according to Example 1 were followed to obtain ultra-low temperature vitrified bond with a grain size of 10-20 μm.
[0079] [Table 7]
[0080] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 390°C and a sintering temperature of 475°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 57 MPa and an impact strength of 9 KJ / m 2 It was.
[0081] 2. Preparation of Ceramic Diamond Wheel Using the above-mentioned ultra-low temperature vitrified bond that had been prepared in mass fraction, and according to the preparation process and parameters of the ceramic diamond wheel of Example 2, an ultra-fine abrasive ceramic diamond wheel was obtained with a spherical pore shape, a porosity of 60 vol%, and a pore size of 35 to 470 μm.
[0082] [Example 8] 1. Preparation of Bond The raw materials were blended according to the mass fractions shown in Table 8 below, and the preparation process and parameters of the bond according to Example 1 were followed to obtain ultra-low temperature vitrified bond with grain size of 10-20 μm.
[0083] [Table 8]
[0084] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 335°C and a sintering temperature of 425°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 48 MPa and an impact strength of 7 KJ / m 2 It was.
[0085] 2. Preparation of Ceramic Diamond Wheel Using the above-mentioned ultra-low temperature vitrified bond that had been prepared in mass fraction, and according to the preparation process and parameters of the ceramic diamond wheel of Example 2, an ultra-fine abrasive ceramic diamond wheel was obtained with a spherical pore shape, a porosity of 70 vol%, and a pore size of 35 to 470 μm.
[0086] [Example 9] 1. Preparation of Bond The raw materials were blended according to the mass fractions shown in Table 9 below, and the preparation process and parameters of the bond according to Example 1 were followed to obtain ultra-low temperature vitrified bond with a grain size of 10-20 μm.
[0087] [Table 9]
[0088] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 350°C and a sintering temperature of 445°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 49 MPa and an impact strength of 7 KJ / m 2 It was.
[0089] 2. Preparation of Ceramic Diamond Wheel Using the above-mentioned ultra-low temperature vitrified bond that had been prepared in mass fraction, and according to the preparation process and parameters of the ceramic diamond wheel of Example 2, an ultra-fine abrasive ceramic diamond wheel was obtained with a spherical pore shape, a porosity of 70 vol%, and a pore size of 35 to 470 μm.
[0090] [Comparative Example 1] 1. Preparation of Bond The raw materials were mixed according to the mass fractions shown in Table 10 below, and the mixed materials were mixed uniformly using a three-dimensional mixer, and dehydrated in a high-temperature oven at a temperature of 400 ° C for 60 minutes. Then, in a high-temperature smelting furnace, a quartz crucible was used to melt the mixture at a temperature of 1100 ° C for 40 minutes to obtain molten glass, and the molten glass in the molten state was put into water to perform water quenching, and then finely ground using a stirring mill (the rotation speed of the stirring mill was 840 rpm, wet milling was used, the mass ratio of water to material was 1:1, the polishing medium was a zirconia ball with a diameter of 5 to 7 mm, and the ratio of ball to material was 3:1), ball milling was performed for 1 hour, and the mixture was dried at a temperature of 150 ° C for 10 hours to obtain an ultra-low temperature vitrified bond with a particle size of 10 to 20 μm.
[0091] [Table 10]
[0092] The ultra-low temperature vitrified bond prepared in this example had a softening temperature of 610°C and a sintering temperature of 720°C. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 40 MPa and an impact strength of 2 KJ / m 2 It was.
[0093] 2. Preparation of Ceramic Diamond Wheel According to the method and process of preparing the wheel in Example 2, the wheel materials were blended, mixed, granulated, molded and dried, and then placed in a furnace to be sintered in an air atmosphere at a sintering temperature of 720°C and a heat retention time of 3.5 hours. As shown in FIG. 2(b), the structure of the sintered body was destroyed and it was unusable.
[0094] [Comparative Example 2] 1. Preparation of Bond In this comparative example, a vitrified bond prepared by the same process as in Comparative Example 1 was used.
[0095] 2. Preparation of Ceramic Diamond Wheel According to the wheel preparation plan and process of Example 1, the wheel materials are blended, mixed, granulated, molded and dried, and then placed in a furnace to be sintered under air atmosphere, the sintering temperature is 720℃, the warming time is 3.5 hours, and the wheel porosity is only 30vol%, and the pore size is 10-40μm, to obtain an ultrafine abrasive ceramic diamond wheel. The reason is that the sintering temperature of the bond is much higher than the burning temperature of the pore-forming agent, so after the pore-forming agent is burned, a large amount of the pore structure at the position where it is located cannot be maintained, and the higher the sintering temperature of the bond is than that of the pore-forming agent, the lower the porosity obtained.
[0096] [Comparative Example 3] 1. Preparation of Bond The raw materials were mixed according to the mass fractions shown in Table 11 below, the mass ratio of Bi2O3 to ZnO was 9.6:1, the mixed materials were mixed uniformly using a three-dimensional mixer, and decrystallized water was performed in a high-temperature oven at a temperature of 400 ° C for 60 minutes. Then, in a high-temperature smelting furnace, a quartz crucible was used to melt the mixture at a temperature of 900 ° C for 120 minutes to obtain molten glass, and the molten glass in the molten state was put into water and water quenched, and then finely ground using a stirring mill (the rotation speed of the stirring mill was 840 rpm, wet milling was used, the mass ratio of water to material was 1: 1, the polishing medium was a zirconia ball with a diameter of 5 to 7 mm, and the ratio of ball to material was 3: 1), ball milling was performed for 1 hour, and the mixture was dried at a temperature of 150 ° C for 10 hours to obtain an ultra-low temperature vitrified bond with a particle size of 10 to 20 μm.
[0097] [Table 11]
[0098] The ultra-low temperature vitrified bond prepared in this embodiment had a softening temperature of 340°C, a sintering temperature of 430°C, and a fluidity of 90% at a temperature of 430°C, which was in the melting start state and had normal fluidity. The strength test piece made of the ultra-low temperature vitrified bond and diamond prepared in this example has a flexural strength of 45 MPa and an impact strength of 5 KJ / m 2 It was.
[0099] 2. Wheel Preparation The above-mentioned ultra-low temperature vitrified bond thus prepared is weighed out at 25% by mass, diamond abrasive with a particle size of 0-0.5 μm at 20%, and polytetrafluoroethylene polymer pore former with a particle size of 30-300 μm at 55% by mass, and the above materials are uniformly mixed to obtain a mixed material for the wheel. The mixed material is then wetted for 10 minutes with a 10% phenolic resin alcohol solution (concentration 35%) added to the mass of the mixed material, and passed through a 60 mesh sieve five times to perform uniform mixing and granulation. The granulated mixed material is then subjected to a 1000 g / kg weight test. The wheel was molded and pressed, dried, and then sintered in an air atmosphere in a furnace. The sintering temperature was 400°C and the heat retention time was 5 hours. The wheel had a porosity of 80vol%, and the pore structure was normal (see Figure 10). There was significant pore fusion, and the pore structure was incomplete in some places. The reason for this was that the sintering temperature of the bond was higher than the burning temperature of the pore-forming agent, and the structure of the corresponding area could not be maintained after the pore-forming agent was burned off.
[0100] Application test: Grinding performance of ultra-fine grain vitrified bond diamond wheel A grinding performance test was carried out using a wafer grinding machine for the ultrafine grain vitrified bond diamond wheels prepared in Examples 1, 2, 3, 4, 5, 6, 7 and Comparative Examples 2 and 3. An 8-inch silicon wafer was ground with the wheel, and the current value, wear, surface roughness, damage layer, etc. were measured when the grinding allowance of the silicon wafer was 15 μm. The measurement results are shown in Table 12 below.
[0101] [Table 12]
[0102] As can be seen from Table 12, the ultrafine abrasive vitrified bond diamond wheel according to the present invention has spherical pores which are advantageous for the structural strength of the wheel, so that when grinding silicon wafers, the grinding performance is good, the feed rate is relatively fast, and the processing damage is relatively low. The wheel with grain size M2 / 4 according to Example 1 has a feed rate of 2 μm / s and a damage layer thickness of 2.6 μm or more. The wheel with grain size M1 / 2 according to Example 2 has a feed rate of 0.5 μm / s and a damage layer thickness of 1.2 μm or more. The wheel with grain size M0 / 0.5 according to Example 3 has a feed rate of 0.4 μm / s and a damage layer thickness of 0.6 μm or more. In contrast, the wheel according to Comparative Example 2 has a grain size of M2 / 4, but the sintering temperature of the bond is relatively high, which is much higher than the burnout temperature of the pore-forming agent, so the porosity of the wheel is relatively low, which is unfavorable to the grinding performance of the wheel, and the feed rate is 0.6 μm / s and the damage layer thickness is 8.40 μm, which is significantly different from Examples 1, 4, 5, and 6. Comparative Example 1 uses a vitrified bond similar to Comparative Example 2, but the sintering temperature of the vitrified bond used is relatively high, so a wheel with a high porosity of 70% or more could not be prepared, and a comparison test of the grinding performance could not be performed. The wheel according to Comparative Example 3 has a grain size of M0 / 0.5, and the bond strength is lower than that of Example 3, and the sintering temperature is higher than that of Example 3, so the prepared wheel has an unideal pore structure, and the feed rate is 0.15 μm / s and the damage layer thickness is 1.42 μm, which is significantly different from Example 3.
Claims
1. As a component, by mass fraction, Bi 2 O 3 : 40-80%, B 2 O 3 :5~15%, ZnO:10~35%, SiO 2 : 0 to 5%, Li 2 O: 0.5-3%, TiO 2 : 0-5%, CaF 2 : 2 to 10% and Y 2 O 3 : 0 to 5% included A super-low temperature vitrified bond characterized by:
2. As a component, by mass fraction, Bi 2 O 3 : 40-70%, B 2 O 3 : 5-12.5%, ZnO: 12.5-35%, SiO 2 : 1 to 5%, Li 2 O: 0.5-3%, TiO 2 : 0-5%, CaF 2 : 2 to 10% and Y 2 O 3 : 0 to 5% included 2. The ultra-low temperature vitrified bond according to claim 1 .
3. Bi 2 O 3 and ZnO have a mass ratio of 1.5 to 5.5:
1.
2. The ultra-low temperature vitrified bond according to claim 1 .
4. a. Particle size is 10-20 μm; b. The softening point is 320 to 395°C; c. The sintering temperature is 400 to 485°C; Satisfy at least one of the characteristics a to c 2. The ultra-low temperature vitrified bond according to claim 1 .
5. Bi 2 O 3 : 40-80%, B 2 O 3 :5~15%, ZnO:10~35%, SiO 2 : 0 to 5%, Li 2 O: 0.5-3%, TiO 2 : 0-5%, CaF 2 : 2 to 10% and Y 2 O 3 (1) uniformly mixing raw materials at a mass fraction of 0 to 5% to obtain a mixed material; (2) melting the mixed material at a temperature of 900 to 1100° C. for 40 to 120 minutes to obtain molten glass; (3) water quenching the molten glass, grinding it using a stirring mill, and drying it to obtain a super-low temperature vitrified bond with a grain size of 10-20 μm. A method for preparing an ultra-low temperature vitrified bond, comprising:
6. a. The mass fraction of the raw material is Bi 2 O 3 : 40-70%, B 2 O 3 : 5-12.5%, ZnO: 12.5-35%, SiO 2 : 1 to 5%, Li 2 O: 0.5-3%, TiO 2 : 0-5%, CaF 2 : 2-10%, Y 2 O 3 : 0 to 5%; b. Bi of the raw material 2 O 3 and ZnO in a mass ratio of 1.5 to 5.5:1; c.B 2 O 3 Instead of using boric acid as the initial raw material, the amount of boric acid used is B 2 O 3 It is 1.8 times d. Li 2 Lithium carbonate is used as the initial raw material instead of O, and the amount of lithium carbonate used is Li 2 It is 2.47 times that of O. e. Using at least one of boric acid and lithium carbonate as an initial raw material, removing water of crystallization from the mixed material at a temperature of 350 to 450°C, and melting the mixed material at a temperature of 900 to 1100°C for 40 to 120 minutes to obtain a molten glass; Satisfy at least one of the characteristics a to e 6. The method for preparing a vitrified bond at ultra-low temperature according to claim 5.
7. In step (3), the polishing parameters by the stirring mill are: the rotation speed of the media stirring mill is 800-900 rpm; wet milling is used; the mass ratio of water to material is 1-1.5:1; the polishing medium is zirconia balls; the mass ratio of balls to material is 2-4:1; and ball milling is performed for 0.5-2 hours.
6. The method for preparing a vitrified bond at ultra-low temperature according to claim 5.
8. The ultra-low temperature vitrified bond according to any one of claims 1 to 4 is included. A ceramic diamond wheel characterized by:
9. The ceramic diamond wheel contains 15 to 35 parts by mass of ultra-low temperature vitrified bond and 20 to 75 parts by mass of diamond abrasive, and the porosity of the ceramic diamond wheel is 35 to 95 vol%.
9. The ceramic diamond wheel according to claim 8.
10. The diamond abrasive has a particle size of 0.5 to 5 μm.
9. The ceramic diamond wheel according to claim 8.
11. a. The porosity of the ceramic diamond wheel is 40 to 95 vol%, 70 to 95 vol%, or 75 to 95 vol%, b. The pore size is 20 to 800 μm and can be controlled as necessary; Satisfy at least one of the characteristics a to b 9. The ceramic diamond wheel according to claim 8.
12. 9. A method for preparing a ceramic diamond wheel according to claim 8, comprising the steps of: The raw materials are uniformly mixed in mass fractions of 15-35% ultra-low temperature vitrified bond, 20-75% diamond abrasive, and 10-55% polymer pore former to obtain a mixed material, which is then wetted with 5-10% phenolic resin alcohol solution based on the mass of the mixed material, sieved, and granulated. The granulated mixed material is press molded and dried, and then sintered at a temperature of 400-485°C in an air atmosphere, and the temperature is kept for 3.5-5 hours to obtain a ceramic diamond wheel.
1. A method for preparing a ceramic diamond wheel, comprising:
13. The polymeric pore-forming agent is one or both of polyethylene particles and polytetrafluoroethylene particles, and the particle size of the polymeric pore-forming agent is 20 to 400 μm.
13. The method of claim 12, wherein the ceramic diamond wheel is prepared by the steps of:
Citation Information
Patent Citations
Self-sharpening diamond grinding wheel and preparation technology thereof
CN109333386A
Low-temperature ceramic bond diamond grinding wheel and preparation method thereof
CN115284186A
Abrasive grain with vitrified bond and filler
JP2020506280A
Fixed-abrasive NANO-grinding plates, related articles, and related methods
WO2024112735A1
Low-temperature sintered ceramic binding agent and preparation technique thereof
CN107617983A
Cited By
SiO2 ceramic bond grinding tool and preparation method thereof
CN120551961A
A composite grinding wheel based on ceramic material and a method for producing the same
CN122606490A